Manganese-mediated reductive functionalization of activated aliphatic acids and primary amines - Zhan Li (Nature Portfolio, 2020)
Alkyl carboxylic acids and primary amines are ubiquitous and useful for synthesis of new compounds. Here, the authors report a manganese-mediated reductive decarboxylative/deaminative functionalization of activated aliphatic acids and primary amines for construction of C-C and C-X bonds under mild conditions.